2002
DOI: 10.1002/1521-3773(20021004)41:19<3645::aid-anie3645>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Rate Enhancements and Improved Diastereoselectivities through Chelating Diamide Coordination in Intramolecular Alkene Hydroaminations Catalyzed by Yttrium and Neodymium Amido Complexes

Abstract: The catalyzed intramolecular hydroamination of carbon± carbon multiple bonds is one of the most important methods for the synthesis of nitrogen heterocycles. [1] Of the variety of metal-based catalysts for this transformation, complexes of the lanthanides appear uniquely well suited for effecting chemoselective alkene hydroaminations under mild reaction conditions. [2, 3] The vast majority of the complexes that have found utility for this purpose are comparatively air-and moisture-sensitive metallocene deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 0 publications
6
77
1
Order By: Relevance
“…Additionally, epimerization of C 1 -symmetric lanthanide-based systems was often observed in the presence of donor molecules, contributing to lowered enantioselectivities. More recently, Livinghouse and coworkers have revealed that non-cyclopentadienyl based systems such as C 2 -symmetric bis-amides [12] and chelating bis-thiophosphinic amidates [13] result in improved stereoselectivities and substantially increased catalytic activities, suggesting that complicated multistep syntheses and separation of chiral ligand systems are not necessary. Similarly promising results have been communicated for lanthanide systems bearing polydentate Schiff base ligands such as salicylaldimine [14], and this chemistry has recently been extended to include the binaphthyl diamine [15], biphenolate and binaphtholate families [16].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Additionally, epimerization of C 1 -symmetric lanthanide-based systems was often observed in the presence of donor molecules, contributing to lowered enantioselectivities. More recently, Livinghouse and coworkers have revealed that non-cyclopentadienyl based systems such as C 2 -symmetric bis-amides [12] and chelating bis-thiophosphinic amidates [13] result in improved stereoselectivities and substantially increased catalytic activities, suggesting that complicated multistep syntheses and separation of chiral ligand systems are not necessary. Similarly promising results have been communicated for lanthanide systems bearing polydentate Schiff base ligands such as salicylaldimine [14], and this chemistry has recently been extended to include the binaphthyl diamine [15], biphenolate and binaphtholate families [16].…”
Section: Introductionsupporting
confidence: 74%
“…The La1-I1 distance of 3.1628 (18) A is intermediate between those determined for complexes 1 and 2 and is similar to La-I parameters reported for related cyclopentadienyl-supported compounds. The La-N anilido bond length of 2.324 (12) A may be compared with values of 2.347(4) and 2.360(3) A for the terminal metal-anilido linkages in dimeric La 2 (NHAr) 6 and are in agreement with those found in the monomeric base adducts La(NHAr) 3 (THF) 3 and La(NHAr) 3 …”
Section: Resultsmentioning
confidence: 99%
“…Although early studies were conducted with configurationally unstable cyclopentadienyl-based ligands4, in 2001, Livinghouse and co-workers demonstrated that cyclopentadienyl ligands are not necessary for catalytic hydroamination6,7 and new, more stable chiral catalysts were subsequently developed.…”
Section: Oxidatively Neutral Cyclizationsmentioning
confidence: 99%
“…Hydroamination of 1 proceeded very slowly with 5 mol % of Y[N(SiMe 3 ) 2 ] 3 (744 h) at 60 • C in C 6 D 6 , while a complex prepared in situ from Y[N(SiMe 3 ) 2 ] 3 and bidentate aniline ligand 3a completed the reaction within 15 min under the same reaction conditions (eq 1). 6 By modifying the ligand structure with a different linker and substituents on the aromatic ring, the reactivity of the yttrium complex can be readily modified. Using alkene 4 to form a piperidine ring, an Y[N(SiMe 3 ) 2 ] 3 /ligand 3b complex showed the highest reactivity; the reaction was complete within 15 min at 120 • C (eq 2).…”
Section: Functionalization Of Alkenes and Alkynesmentioning
confidence: 99%